DEVELOPMENT OF VOCATIONAL EDUCATION IN THE CONDITIONS OF WORLD INTEGRATION PROCESSES - Kira B. Prigozhina (Образование и наука)
Abstract. The present publication is devoted to overview and analysis of modern integration processes and their influence on educational system.The aim of the publication is to reveal the main problems which the educational sphere in connection with the accruing globalization tendencies faces; to designate the ways of international cooperation in the field of the higher education.Methods. The methods involve problem and comparative analysis, empirical observation, and data processing. Scientific works on the theory of integration, the concept of global education, culture of international communication have formed methodological base of studying of the considered problems.Results and scientific novelty. The essence of a phenomenon of globalization is disclosed. The reasons of transformation of national education systems under the influence of globalization processes are described; the tendencies and spheres of this influence are analysed. The international experience of the solution of the arising problems in connection with globalization of education market and a general crisis of education is summarized. The features of development of professional training in a situation of interaction of cultures are considered; the forms and possibilities of international cooperation in the field of the higher education on the basis of integration of national and international achievements are pointed out.Practical significance. The materials of the article can be useful to the researchers who are engaged in studying of aspects of globalization of world economic space and also specialists of management of education in case of development strategies of educational structures and separate organizations.